Understanding the role of the dye/oxide interface via SnO2-based MK-2 dye-sensitized solar cells. Issue 23 (21st June 2015) - Son, Dae-Yong; Lee, Chang-Ryul; Shin, Hee-Won; Jang, In-Hyuk; Jung, Hyun Suk; Ahn, Tae Kyu; Park, Nam-Gyu
<x xml:space="preserve">Abstract</x> The interfacial blocking layer between dye and oxide was found to play crucial roles in retarding recombination, increasing diffusion, accelerating dye regeneration and narrowing the density of states.